Quantitative determination of artificial sweeteners and sucrose in energy drinks and mango juice available in Dhaka city by UV-Spectrophotometric method - Kanon, Kabirul Islam (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.